Going rogue : an American life - Palin, Sarah, 1964- (New York : Harper, 2009)
Sarah Palin, the first female Republican Vice Presidential candidate, recounts her political experiences, her rapid rise on the national stage during the 2008 campaign, and the personal challenges she's faced including balancing her time as a working mother, recognizing the war's impact with her son serving combat in Iraq, having a child with a disability, and supporting her teenage daughter with an unplanned pregnancy.
The last frontier -- Kitchen-table politics -- Drill, baby, drill -- Going rogue -- The thumpin' -- The way forward -- Epilogue -- A view from Alaska / Dewey Whetsell.
Keywords: Palin, Sarah, -- 1964-; Governors -- Alaska -- Biography; Vice-presidential candidates -- United States -- Biography; Women conservatives -- United States -- Biography; Women politicians -- United States -- Biography; Alaska -- Biography; Alaska -- Politics and government -- 1959-; Republican Party (U.S. : 1854- ) -- Biography; United States -- Politics and government -- 1989- -- Personal narratives; Palin, Sarah; USA; Geschichte 1964-2009